2024
DOI: 10.1007/s12550-024-00525-6
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is a “brake” in JNK-mediated activation of amyloid protein precursor and hyperphosphorylation of tau induced by T-2 toxin in BV2 cells

Yingying Zhao,
Martin Valis,
Xu Wang
et al.

Abstract: Mycotoxins have the capacity of triggering neurodegenerative conditions like Alzheimer's disease (AD), which is marked by β-amyloid (Aβ) deposition and hyperphosphorylation of tau (P-tau). However, there is no evidence of an exact molecular mechanism to prove the above point. Due to the high toxicity and broad contamination of T-2 toxin, we assessed how T-2 toxin exposure alters amyloid precursor protein (APP) and P-tau formation in BV2 cells, and determined the underlying roles of HIF-1α and JNK3 signaling. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In Zhao et al’s (2024) study, they found the level of hyperphosphorylated tau induced by T-2 toxin increased when HIF-α signaling was inhibited. This suggested that HIF-1α played a protective role in the T-2 toxin-induced expression of hyperphosphorylated tau ( Zhao et al, 2024 ). Taken together, we have sufficient reasons to believe that HIF-1α is associated with tau pathology in AD, however, the specific mechanism remains unclear and requires further research.…”
Section: Hif-1α Is An Essential Factor In Ad Onsetmentioning
confidence: 99%
See 2 more Smart Citations
“…In Zhao et al’s (2024) study, they found the level of hyperphosphorylated tau induced by T-2 toxin increased when HIF-α signaling was inhibited. This suggested that HIF-1α played a protective role in the T-2 toxin-induced expression of hyperphosphorylated tau ( Zhao et al, 2024 ). Taken together, we have sufficient reasons to believe that HIF-1α is associated with tau pathology in AD, however, the specific mechanism remains unclear and requires further research.…”
Section: Hif-1α Is An Essential Factor In Ad Onsetmentioning
confidence: 99%
“…After entering the brain, T-2 toxin can cause further damage by triggering oxidative stress, neuroinflammation, and even apoptosis and it can also induce the rise of phosphorylated tau protein. A study has found that T-2 toxin can induce the expression of hyperphosphorylated tau ( Zhao et al, 2024 ). In Zhao et al’s (2024) study, they found the level of hyperphosphorylated tau induced by T-2 toxin increased when HIF-α signaling was inhibited.…”
Section: Hif-1α Is An Essential Factor In Ad Onsetmentioning
confidence: 99%
See 1 more Smart Citation